(untitled) (PerCursos, 2022)
This article sought to know the different occupations and the profile of workers in the textile handicraft sector in Resende Costa (MG), highlighting the female participation in the maintenance of this praxis. Data from the 2010 Demographic Census of the IBGE was used, as it was the only possible source to analyze the municipality of interest. Among the main results, we highlight that at least four occupations linked to the handicraft sector were mapped in the Classification of Occupations for Household Surveys used by IBGE. Work in the handicraft sector in the municipality is characterized by being mostly informal and with low wages. Although women represent 63% of the labor force in this sector, their income is almost half of what men receive. The main result is that the textile handicraft sector is marked by significant gender differences in Resende Costa.